Shariah-Compliant Digital Marketing in Early Childhood Education: A Case Study from Malaysia - Nurma Sari; Rahmayati Rahmayati (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2025)
Digital marketing has become a crucial tool for educational institutions to increase visibility, build trust, and attract prospective students. However, the integration of Sharia principles into digital marketing remains underexplored, particularly in early childhood education. This study aims to analyze the implementation of Sharia-based digital marketing strategies at Tadika Tinta Khalifah School, Kedah, Malaysia. Employing a descriptive qualitative approach, data were collected through interviews, observations, and documentation to provide a comprehensive understanding of marketing practices within the school context. The findings reveal that the school employs social media platforms, an official website, and Islamic value-based content as its primary marketing strategies. These practices reflect adherence to Sharia principles such as honesty, transparency, and ethical communication. Nonetheless, the study also identifies several challenges: limited human resources, constrained promotional budgets, strong competition from other schools, and the need for parents to adapt to digital platforms. Despite these obstacles, the results show that the school has effectively utilized digital marketing in ways that both promote its services and preserve Islamic ethical standards. The contribution of this study lies in offering practical insights into how Sharia-compliant digital marketing can be applied in early education, highlighting both its opportunities and constraints. It provides valuable recommendations for strengthening capacity, optimizing content, and fostering collaboration to enhance competitiveness while maintaining alignment with Islamic values.